2011
DOI: 10.1007/s10067-011-1858-3
|View full text |Cite
|
Sign up to set email alerts
|

Monthly or weekly bisphosphonate? Evaluation of satisfaction in patients with postmenopausal osteoporosis using OPSAT-Q questionnaire during the BOOSTER study in Croatia

Abstract: A prospective, open-labelled, multicentre 6-month study was designed to assess three categories that have high impact on Health-Related Quality of Life (HR-QoL). These categories were: satisfaction, preference and drug tolerability in postmenopausal patients with osteoporosis in Croatia, at first treated with weekly oral bisphosphonates, followed by monthly oral ibandronate. Three hundred eighty-five postmenopausal women who were treated with one of the weekly bisphosphonates for at least 6 months were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the clinical studies, the following questionnaires were used: Beliefs about Medicines Questionnaire (BMQ, including 22 questions in the following major domains: the necessity of the prescribed medication to manage osteoporosis now and in the future, concerns about the potential adverse effects of taking the prescribed medication, preference for one medication over the other) [ 24 , 25 ], Preference Satisfaction Questionnaire (PSQ, measuring preference, pill satisfaction, injection satisfaction, pill bother and injection bother) [ 25 28 ], questionnaires for preference adapted from Balto I and II [ 29 31 ], Osteoporosis Patient Satisfaction Questionnaire (OPSATQ) [ 26 , 32 ] and Treatment Satisfaction Questionnaire for Medication (TSQM; consisting of 14 items to assess an individual’s perception of effectiveness, side effects, convenience and global satisfaction) [ 33 ].…”
Section: Patients’ Preferences For Osteoporosis Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical studies, the following questionnaires were used: Beliefs about Medicines Questionnaire (BMQ, including 22 questions in the following major domains: the necessity of the prescribed medication to manage osteoporosis now and in the future, concerns about the potential adverse effects of taking the prescribed medication, preference for one medication over the other) [ 24 , 25 ], Preference Satisfaction Questionnaire (PSQ, measuring preference, pill satisfaction, injection satisfaction, pill bother and injection bother) [ 25 28 ], questionnaires for preference adapted from Balto I and II [ 29 31 ], Osteoporosis Patient Satisfaction Questionnaire (OPSATQ) [ 26 , 32 ] and Treatment Satisfaction Questionnaire for Medication (TSQM; consisting of 14 items to assess an individual’s perception of effectiveness, side effects, convenience and global satisfaction) [ 33 ].…”
Section: Patients’ Preferences For Osteoporosis Medicationsmentioning
confidence: 99%
“…The open-label studies included patients who had been on weekly bisphosphonates and who were switched to a monthly regimen [ 26 , 32 , 35 ] or to another bisphosphonate or denosumab [ 33 ] and showed a preference for the less frequently administered treatment. Kendler et al (2011) found no difference in perceived necessity of osteoporosis treatment between 6-monthly injections or weekly oral bisphosphonates at baseline, but after 6 months, the perceived necessity was higher in the denosumab group.…”
Section: Patients’ Preferences For Osteoporosis Medicationsmentioning
confidence: 99%
“…Another strength of our study was the evaluation of HRQoL by means of the mini-OQLQ. Effects of ibandronate on HRQoL have seldom been assessed [15,16]. Our results suggest that all aspects of QoL may improve with ibandronate, which should be a primary goal of antiresorptive therapy according to some authors [17].…”
Section: Discussionmentioning
confidence: 85%
“…Several treatment characteristics that could influence the decision‐making process have been described in the literature: (1) route and frequency of administration 52 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ; (2) efficacy 52 , 57 , 58 , 60 , 61 , 65 , 67 , 69 , 71 , 73 ; (3) cost of treatment (for the patient and for society) 52 , 58 , 62 , 65 , 67 , 71 ; (4) adverse events or side effects 52 , 57 , 58 , 60 , 61 , 63 , 64 , 65 , 67 , 69 , 71 , 72 , 73 , 74 , 75 ; (5) total duration of the treatment 60 ; (6) convenience (i.e., number of pills, independency, dosing facility, body position) 57 , 63 , 64 ...…”
Section: Decision Driversmentioning
confidence: 99%